Hazard assessment of potential debris flow: A case study of Shaling Gully, Lingshou County, Hebei Province, China - Wang, Zhong Fu; Zhang, Xu Sheng; Zhang, Xu Zhu; Wu, Ming Tang; Wu, Bo (Frontiers in Earth Science, 2023)
The debris flows in the Taihang Mountain region in North China are basically triggered by rainstorms. Firstly, the debris flow susceptibility of the Shaling Gully, Lingshou County, Hebei Province, China was analyzed in this paper to evaluate its hazard and effect on the downstream proposed structures. Secondly, the maximum deposition depth and velocity of the potential debris flow in Shaling Gully were numerically simulated based on the FLO-2D model, and the simulation results indicate that the deposition depths under the 50-year and 100-year rainstorms will have some effect on the downstream proposed structures. With debris flow intensity classification, the hazard of potential debris flow in Shaling Gully was classified. According to the deposition depths and velocities simulated by FLO-2D model, the ARCGIS software was adopted to optimize the hazard zones, and therefore the hazard zonation map was established. With consideration of simulation results under natural conditions and other factors such as gully feature, a 4m high and 40m wide retaining dam was designed. The numerical simulation results show that the retaining dam may decrease the debris flow hazard to a negligible level, which offers some beneficial reference to the subsequent engineering design for Shaling Gully..